Lusitanian (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
This paper provides an overview of the current state of knowledge of the Lusitanian language and suggests potentials for further research. It covers the transmission of Lusitanian including the onomastic subsystems, the (historical-comparative) phonology as reflected in the writing system, morphology and lexicon. Emphasis is placed on the sociolinguistic situation and the linguistic affiliation.
Keywords: Lusitanian Sprache; Epigraphy; Onomastics; Linguistic contact; Linguistic affiliation